2006
DOI: 10.4102/sajip.v32i3.437
|View full text |Cite
|
Sign up to set email alerts
|

Importance of apparel store image attributes: Perceptions of female consumers

Abstract: This qualitative research focused on identifying those store image attributes perceived as important by a selected group of female apparel consumers. In addition, their perception of Lindquist’s proposed dimensions of store image attributes was examined. Data were collected by means of eight focus groups. The non-verbal quali-quantive Schutte Visual Scale was employed to quantify responses. Results indicated that Merchandise and Clientele were perceived as the most important dimensions, followed by Service. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 33 publications
4
25
1
2
Order By: Relevance
“…This premise is true only if the store image expectations of customers are in line with their perceptions. Visser et al (2006) explained that the retailer must align the features of the store to attract customers, such that it could become the preferred retailer. Studies on image indicated the influence of stakeholder perceptions on the main features of the firm, and the firm could use this information in formulating management strategies (Markwick & Fill, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…This premise is true only if the store image expectations of customers are in line with their perceptions. Visser et al (2006) explained that the retailer must align the features of the store to attract customers, such that it could become the preferred retailer. Studies on image indicated the influence of stakeholder perceptions on the main features of the firm, and the firm could use this information in formulating management strategies (Markwick & Fill, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…They argue that it is mostly the family and not the individual who is the consumer of the retail offering. Visser et al (2006) studied the importance of apparel store image attributes as perceived by female consumers by means of eight focus groups. Results indicated that merchandise and clientele were perceived as the most important dimensions, followed by service; physical facilities were the least important.…”
Section: Related Studiesmentioning
confidence: 99%
“…Kotler and Keller (2006) defined sales promotions as a diverse collection of incentives, designed to stimulate quicker purchases of particular products or services. Promotion has also been considered as one of the important attributes of store image (Visser, 2006). Consumers are more likely to purchase from a retailer that runs promotion son some of their merchandise (Vipu, 2010).…”
Section: Exploratory Factor Analysismentioning
confidence: 99%